From Brand to Customer. (May 2016) - Rao, Ajit
Abstract: This article is about the inevitability of organizations to move away from a production and/or brand mindset to a customer-centric mindset. This article focuses on how an organization can build and manage such customer-oriented culture. Given that what is measured gets managed, the article starts with a discussion on the key metrics—customer metrics—that need to be defined, measured, discussed and driven within the organization. The article then explores the options available for any organization to enhance the customer metrics more specifically through customer experience and relationship building. The article is written keeping in mind the working executives. This article is based on the author's experiences, observations and formal and informal discussions with his clients and non-clients.